Emotionally intelligent leadership : a guide for students - Levy Shankman, Marcy; Allen, Scott J., 1972-; Allen, Scott J.; Haber-Curran, Paige (San Francisco, CA : A Wiley Brand, 2015)
"Explores the connection between emotional intelligence and effective leadership"--
Includes bibliographical references and index.
Keywords: Educational leadership; Teacher effectiveness; Emotional intelligence; EDUCATION / Students & Student Life; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Leadership